Conceptualising lifelong learning: The case of lifelong learning practices at Universiti Utara Malaysia - Ang, Chooi Leng; Thi, Lip Sam; Pillai, Padmini; Abdul Rahman, Hamzah; Don, Mohd Sobri (Common Ground Publishing, 2009)

(untitled)
This paper discusses the concept of lifelong learning and the approach to it by Universiti Utara Malaysia’s Executive Development Centre (EDC). It illustrates how a university adopts an indigenous approach that delivers lifelong learning programmes and its implication for working adults. Generally, Universiti Utara Malaysia and other public universities in Malaysia are non-profit making institutions. Currently, EDC is offering more than twenty five (25) executive diplomas and certificate courses. The target students are working adults who wish to upgrade their management skills and knowledge. For this purpose, EDC has forged strategic alliances with several training providers and in tandem, draws up courses geared towards working adults. In working with education providers, EDC closely monitors the courses managed by its partners. The mode of delivery is face-to-face interaction during classes that are held during weekends once every month. The duration of the programmes may last from a few weeks to a year depending on the number of modules the students are required to complete. All courses are subjected to formal evaluation to show proof of students acquiring the requisite knowledge before they are conferred certificates or executive diplomas.